2018
DOI: 10.3382/ps/pey046
|View full text |Cite
|
Sign up to set email alerts
|

Forsythia suspensa extract protects broilers against breast muscle oxidative injury induced by corticosterone mimicked pre-slaughter acute stress

Abstract: Broilers were used to determine the protective effects of Forsythia suspensa extract (FSE) against breast muscle oxidative injury induced by corticosterone (CS) mimicking pre-slaughter acute stress. A total of 144 male Arbor Acre broilers was randomly allotted to one of 4 treatments in a 2 × 2 factorial arrangement that included FSE supplementation (0 or 100 mg/kg) and subcutaneous injection of CS (0 or 4 mg/kg) at 3 h before slaughter. Corticosterone increased live BW loss, and the adverse effect was attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
1
9
1
Order By: Relevance
“…(2017b) , who reported that the antioxidant properties of FSE as antioxidants could improve postslaughter meat quality in broilers subjected to stress. However, in the present study, there were no significant differences in redness, yellowness, pH at 45 min, pH at 24 h, δpH, and drop loss among treatments, which disagreed with the results of Pan et al., 2018a , Pan et al., 2018b . These differences might be due to the current study conducted under nonchallenge conditions, while other studies were carried out under dexamethasone- or corticosterone-challenge condition.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…(2017b) , who reported that the antioxidant properties of FSE as antioxidants could improve postslaughter meat quality in broilers subjected to stress. However, in the present study, there were no significant differences in redness, yellowness, pH at 45 min, pH at 24 h, δpH, and drop loss among treatments, which disagreed with the results of Pan et al., 2018a , Pan et al., 2018b . These differences might be due to the current study conducted under nonchallenge conditions, while other studies were carried out under dexamethasone- or corticosterone-challenge condition.…”
Section: Discussioncontrasting
confidence: 99%
“…F. suspensa extracts might also be beneficial to alleviate growth inhibition and immune damage of broilers under heat stress and corticosterone stimulation ( Zeng et al., 2014 , Zhao et al., 2017b ). Previous studies in our laboratory also reported FSE could reduce transport stress, slow down muscle protein degradation and growth inhibition, and improve muscle antioxidant capacity and meat quality in broilers ( Pan et al., 2018a , Pan et al., 2018b ). However, to the best of our knowledge, few studies focus on the possible role for FSE in replacing antibiotics under nonchallenge conditions and the possible mechanism on improvement of performance in broilers.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…A high concentration of urea-N in serum is a risk indicator of cardiovascular diseases, whereas the low concentration of uric acid has protective effects on oxidative stress in body ( Glantzounis et al., 2005 ). In addition, the higher concentration of urea nitrogen in serum was reported as transport stressor in broilers ( Pan et al., 2018a , b ).…”
Section: Discussionmentioning
confidence: 99%